Analisis Cemaran Bakteri Coliform pada Jajanan Sekitar Kampus Universitas Negeri Makassar - Damayanti, Putri (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
The safety of ready-to-eat street food around university campuses is a growing concern due to potential contamination by pathogenic microorganisms, especially coliform bacteria. This study aimed to analyze the microbiological quality of popular street foods consumed by students around Universitas Negeri Makassar using the Total Plate Count (TPC) and Most Probable Number (MPN) methods. Six food samples were collected purposively and tested in the Science Education Laboratory at Universitas Negeri Makassar in April 2025. The TPC method was applied to determine the total number of microorganisms, and the MPN method was used to estimate the presence of coliforms through presumptive, confirmed, and completed tests. TPC results showed that 4 out of 6 samples (66.66%) exceeded the maximum limit set by Indonesian National Standard (SNI 7388:2019), indicating potential food safety risks. The MPN test revealed that 5 of 6 samples tested positive for coliforms, with values ranging from 460 to >1100 MPN/gram, far above the acceptable limit of ≤3 MPN/gram. Confirmation tests using Eosin Methylene Blue Agar (EMBA) identified Escherichia coli through characteristic metallic green sheen colonies in 2 samples, and Enterobacter spp. in 3 samples with purple colonies. Gram staining results confirmed all isolates were Gram-negative rods, consistent with coliform characteristics. These findings indicate a significant risk of microbiological contamination in street foods commonly consumed around the university area. The presence of fecal indicator bacteria such as E. coli reflects poor hygiene in food handling and environmental sanitation. Strengthening food safety education among food vendors and regular monitoring by relevant authorities is essential to protect public health, especially in academic settings